PENGEMBANGAN BAHAN AJAR MATERI BANGUN DATAR DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK UNTUK MEMBELAJARKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Roslian Lubis; Marzuki Ahmad; Anisa Ahmad (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
Abstract This study aims to develop teaching materials for flat shapes using a realistic mathematics education approach to teach students' mathematical problem solving skills and to determine the quality of teaching materials in terms of validity, practicality, and effectiveness. This research is a development research with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects in this study were 28 grade VIII students of SMP Negeri 7 Padang Sidempuan. The research instrument used to measure the quality of teaching materials was in the form of expert validation questionnaires, student response questionnaires and post-test results of students' mathematical problem solving abilities. The expert validation questionnaire was used to measure the validity of the teaching materials while the student response questionnaire was used to measure the practicality of the teaching materials and the post-test results of students' mathematical solving abilities were used to measure the effectiveness of the class VIII students' teaching materials at SMP Negeri 7 Padang Sidempuan. The results of this study indicate that the quality of teaching materials is seen from the validation assessment of material experts with an average score of 75.5%, for the assessment of media experts with an average score of 78.33%, and for the assessment of linguists with an average score amounted to 90.67% with each score included in the eligible criteria. The overall results of the expert's assessment show that the teaching materials developed have